Narratives of Class in New Irish and Scottish Literature From Joyce to Kelman, Doyle, Galloway, and McNamee - McGlynn, M. (New Directions in Irish and Irish American Literature, 2008)
This book argues that the outskirts of cities have become spaces for a new literature beyond boundaries of traditional notions of nation, class, and gender. Includes discussions of Booker Prize winners Roddy Doyle and James Kelman.